Similarities and Differences in Risk and Protective Factors in Teacher Induction for Prospective Elementary and Physical and Health Education Teachers - Leroux, Mylène; Beaudoin, Charlotte; Grenier, Johanne; Turcotte, Sylvain; Rivard, Marie-Claude (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
The growing body of literature on teacher induction barriers has revealed the need to address issues that may lead to negative consequences. Recent research points to an increased interest in teacher resilience, a concept that promotes positive adaptation to counteract these adverse outcomes. However, teacher induction and resilience may differ depending on teaching context. For example, do specialists such as physical and health education teachers experience the same induction situation as generalist teachers? The authors aimed to compare the anticipated risk and protective factors related to the induction of these prospective teachers. The data from two studies were analyzed using thematic coding. The results indicate similarities and differences between the two groups that suggest ways to better support teacher induction.